Inter-organizational imitation: Definition and typology - Bilal Bourkha (Accounting and Financial Control, 2017)
The sustained idea of this article is that the concept of imitation has not been sufficiently developed in the field of strategic management and has often been confused with the notion of mimicry. Therefore, the objective of this research is to emphasize the distinction between different types of imitation unlike a lot of research on companies imitative behavior focused on one type as the perfect imitation. This will clarify ambiguities in the literature on imitation, and show that the mobilization of neo institutional theory is not sufficient to explain all the imitative behavior of organizations in a market.